2009
DOI: 10.1111/j.1439-0507.2009.01818.x
|View full text |Cite
|
Sign up to set email alerts
|

Species distribution and antifungal susceptibility of blood Candida isolates at a tertiary hospital in southern Taiwan, 1999-2006

Abstract: The aim of this study was to evaluate the incidence of candidaemia, consumption of fluconazole and susceptibility of blood Candida isolates at a tertiary hospital. From January 1999 to September 2006, all candidaemic episodes were identified and available strains were evaluated for the susceptibilities of antifungal agents. Annual defined daily doses of antifungal agents were collected. There had been 909 Candida isolates detected from the bloodstream of 843 patients during the study period. Among them, 740 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
11
1
Order By: Relevance
“…As a result, our study may fail to demonstrate a correlation between fluconazole usage and the percentage of fluconazole non-susceptible isolates, given the rate of azole non-susceptible increasing only from 1% to 5% within the study period. Despite considerable variations in fluconazole consumption, fluconazole resistance rate still remains less than 10% among the Candida isolates in Taiwan 12,28. Similarly, our study was unable to demonstrate any association between echinocandins consumption and Candida species echinocandins non-susceptible rate owing to relative low echinocandins non-susceptible rate of Candida species observed in this study.This study has some limitations.…”
contrasting
confidence: 77%
See 3 more Smart Citations
“…As a result, our study may fail to demonstrate a correlation between fluconazole usage and the percentage of fluconazole non-susceptible isolates, given the rate of azole non-susceptible increasing only from 1% to 5% within the study period. Despite considerable variations in fluconazole consumption, fluconazole resistance rate still remains less than 10% among the Candida isolates in Taiwan 12,28. Similarly, our study was unable to demonstrate any association between echinocandins consumption and Candida species echinocandins non-susceptible rate owing to relative low echinocandins non-susceptible rate of Candida species observed in this study.This study has some limitations.…”
contrasting
confidence: 77%
“…Chen et al . reported that poor correlation between consumption of fluconazole and changes of azole resistance over a 8‐year study period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Candida glabrata appears to be the most frequently isolated non-albicans Candida species in Western countries, whereas, in Asia, it is Candida tropicalis (4,7,28,36,40,41). In certain regions, it even surpassed C. albicans to become the most frequently isolated Candida species (4,40).…”
mentioning
confidence: 99%